Community health worker perspectives on advocacy: design-based research to develop a digital advocacy training course - Job, Nophiwe; Johnston, Jamie Sewan; Westgate, Carey; Skinner, Nadine Ann; Ward, Victoria; Ballard, Madeleine, CHW Advisory Group (Frontiers in Public Health, 2024)
Introduction: While community health workers (CHWs) are well-positioned as health advocates, they frequently lack support and feel undervalued. Advocacy training may prepare CHWs to support communities better.Methods: This study uses a design-based research approach to (1) explore how participation in curriculum-development workshops for a digital advocacy course influenced CHWs' (n=25) perceptions of advocacy and (2) describe how CHW involvement shaped course development. Data were collected via five discussion groups and seven surveys over six months.Results: Initially, the CHWs perceived themselves as community-advocates but not as selfadvocates. They increasingly reflected on the merits of advocating for better working conditions and aspired to greater involvement in decision-making. CHWs reflected positively on their advisory role in shaping the course to improve content acceptability and validity.Discussion: Training efforts to engage CHWs in advocacy must overcome systemic barriers and norms internalized by CHWs that deter them from reaching their full potential as advocates.